SELF CENSORSHIP DAN TANGGUNG JAWAB SOSIAL MEDIA MASSA - Artini Artini (BPSDMP Kominfo Jakarta, 2011)
When the press faced a choice to determine the appropriate event for the news, their obligation is not only just present the facts, but also the truth and the effects of the news. This is the importance of journalists’ self censorship and social responsibility to measure and assess the meaning of reporting. The measurement of self censorship itself is self concience and the ethic of press as their moral grip. This research aims to describe the extent of self-censorship among the media in reference to the press ethics, conscience and social responsibility in media coverage. The perspective of meta-analysis was being used in this research by utilizing the results from existing research of STIKOM LSPR 2009 students, the findings of complained cases from Indonesia Press Council (Dewan Pers) 2001-2007, and the results of group discussion between Indonesian dan Australian journalists on 8-11 November 2010 in Canberra and Sydney. The results of this research showed that journalists prefer to play their role as media demand and industrial markets. Accordingly, there are many media irrelevances intentionally. The implication of this research was the element of self censorship shoud be inheren as journalists’ intelectual process in playing their role as the spearhead of the mass media and its first loyalty to the truth and to citizens. ABSTRAKKetika pers dihadapkan pada pilihan untuk menentukan peristiwa-peristiwa yang tepat untuk dijadikan berita, kewajiban mereka tidak hanya untuk menyajikan fakta, namun juga kebenaran dan dampak dari berita tersebut. Di sinilah pentingnya sensor pribadi dan tanggung jawab sosial dari jurnalis untuk mengukur dan menilai arti dari sebuah laporan. Pengukuran sensor pribadi itu sendiri didasarkan pada kesadaran pribadi dan kode etik pers sebagai pegangan moral mereka. Penelitian ini bertujuan untuk menggambarkan tingkat sensor pribadi dalam media mengacu pada etika pers, hati nurani, dan tanggung jawab sosial dalam liputan media. Penelitian ini menggunakan perspektif meta-analisis dengan memanfaatkan hasil penelitian yang telah ada sebelumnya yaitu yang dilakukan oleh mahasiswa STIKOM LSPR 2009, temuan kasus dari Dewan Pers 2001-2007, and hasil dari FGD antara jurnalis-jurnalis Indonesia dan Australia pada tanggal 8-11 November 2010 di Canberra dan Sydney. Hasil dari penelitian ini menunjukkan bahwa jurnalis cenderung untuk memainkan fungsinya berdasarkan permintaan media dan kebutuhan pasar. Sejalan dengan itu, ada banyak media yang dengan sengaja bertindak tidak relevan. Impikasi dari penelitian ini yaitu elemen dari sensor pribadi harus menyatu dengan proses intelektualisasi jurnalis dalam memainkan fungsinya sebagai ujung tombak dari media massa dan kesetiaannya pada kebenaran dan masyarakat.